Edupreneurship in Modern Era: A Lesson for Early Childhood Studies - Suhendro, Eko (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – The poverty rate, which has increased since the Covid pandemic and continued with the increase in fuel prices and even the influence of the conflict between Russia and Ukraine, has caused the world’s economy to inflation. Employment opportunities are increasingly limited as companies and various sectors go bankrupt. This study aims to explain the idea of developing edupreneurship in the field of early childhood in the Modern era, which students and Islamic Early Childhood Education (IECE) graduates apply. The edupreneurship course is expected to equip students to improvise with life after graduating from college because it supports the profile of IECE study program graduates to become entrepreneurs.Design/methods/approach – This study uses a qualitative descriptive method. This research uses a qualitative approach to describe developing edupreneurship in early childhood. The subjects in this study are students. Data collection techniques in this study included interviews, group discussion forums, and documentation. Interviews were conducted through direct interviews, face-to-face interviews with research subjects, and discussion group forums involving 64 students.Findings – An important finding in this research is the emergence of business development ideas in the field of edupreneurship that students and alumni can implement. This study concludes that early childhood business ideas that can be developed include the Development of Daycare, Playgroups, Kindergarten, Educational Parks, Content Creators, and Children’s healthy food businesses.Research implications/limitations – This research has a narrow coverage area, so the study results are not intended to draw general conclusions or generalizations. However, the results of this study are expected to be used to overcome the problems.Practical implications – The results of this study are expected to provide an overview of the development of edupreneurship for prospective educator students so that the emergence of a graduate profile can realize the learning outcomes of the study program according to the independent learning curriculum as an entrepreneur.Originality/value – Further research recommend to deepen the implementation of the idea of developing edupreneurship in this digital era.Paper type: Case study